1996
DOI: 10.1136/gut.38.6.894
|View full text |Cite
|
Sign up to set email alerts
|

Antineutrophil cytoplasmic antibodies in sera from colectomised ulcerative colitis patients and its relation to the presence of pouchitis.

Abstract: Background-Few studies have evaluated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 23 publications
1
22
0
4
Order By: Relevance
“…Of 250 unique studies identified using the search strategy, 11 studies met the inclusion criteria and were included in the meta‐analysis (eight cohort, three case–control) . There were no randomised controlled trials that addressed this question.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 250 unique studies identified using the search strategy, 11 studies met the inclusion criteria and were included in the meta‐analysis (eight cohort, three case–control) . There were no randomised controlled trials that addressed this question.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, anti‐ Saccharomyces cerevisiae antibody (ASCA) directed against a cell‐wall component of the yeast, S. cerevisiae , is more specific for CD (seen in 29–69% patients) and uncommon in UC (0–29%). Some studies have shown that the presence of ANCA, especially in high titre, may increase the risk of pouchitis after IPAA, but the results have been conflicting . ASCA‐positivity has been associated with an increased risk of post‐operative fistulae and CD‐like condition of the pouch, but it is unclear whether it influences the risk of pouchitis.…”
Section: Introductionmentioning
confidence: 99%
“…UC-ANCA have not been shown to impair neutrophil function,7 their presence is not related to the severity or extent of the disease,3 17 18and in a high percentage of patients they may remain for years after colectomy 1718 This evidence argues against a decisive role of UC-ANCA in tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…An association of atypical pANCA with a more refractory type of disease and with the development of pouchitis after colectomy has been described [30,[36][37][38][39]. The association with pouchitis, however, has not been found in other studies [40,41]. In CD, ANCA have been found in a subgroup of patients, termed UC-like CD, characterized by left-sided colonic inflammation, rectal bleeding, mucus discharge, urgency and treatment with topical agents [42].…”
Section: Auto-antibodies Atypical Pancamentioning
confidence: 97%